Can Husserl’s Phenomenological Method Be Used in Psychological Research? - Lopez Calvo de Feijoo, Ana Maria (2017)
This article aimed to discuss the possibility of making use of Husserl’s phenomenological method in psychology research. Initially, we will present Husserl’s phenomenology project taking into consideration his analysis related to intentionality, the phenomenological method and the reduction of the empirical to the phenomenological. Considering these conceptions, we will discuss the pretensions of Amedeo Giorgi in using the phenomenological empirical method in their psychological research. We will take a closer look on how Amedeo Giorgi applies the phenomenological method in psychological research in order to show its essential but also ambiguous moments. Finally, we will raise questions and suggest answers regarding the possibility of applying Husserl’s method in psychological research.